Effects of regularity on the processing of sound omission in a tone sequence in musicians and non‐musicians. Issue 5 (14th May 2013) - Ono, Kentaro; Matsuhashi, Masao; Mima, Tatsuya; Fukuyama, Hidenao; Altmann, Christian F.
Abstract Numerous studies have reported that perceptual grouping affects the pre‐attentive processing of sound omission in a sequence of tones. However, it remains unclear whether or not the perceptual grouping and musical experience affect the attentive processing of sound omission. To this end, we created a sequence of loud (L) and soft (S) tones grouped as 'LLSLLS…' and a random sequence of the L and S tones. The omission of the L tones was inserted pseudo‐randomly in the random sequence, and there were two positions at which it was inserted. For within‐group omission, the omission was after the first L tone within the 'LLS' pattern. For between‐group omission, the omission was inserted between the patterns. The brain response to the omission in musicians and non‐musicians was measured using magnetoencephalography. During the magnetoencephalography measurement, the subjects' performance in a task to detect the omission was faster in the random sequence than in the group sequence. Source analysis showed that the omission in the random sequence caused greater activity than that in the group sequence. The increase was found in the right inferior parietal lobe in musicians, whereas it was found in the left superior temporal gyrus in non‐musicians. These results suggest that the attentive processing of perceptual grouping might implicate the left superior temporal gyrus or right inferior parietal lobe, depending on musical experience.